Integrated Soil and Water Management: Selected Papers from 2016 International SWAT Conference - Karim Abbaspour (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Soil and water are two key life-sustaining resources on Earth. If not protected, both elements will become humanity's worst nightmares. Uncontrollable water flows, polluted water, and lack of water on the one hand, and infertile soils, polluted soils, dust-storms, and topsoil erosion, on the other hand, can wreak havoc on human life and threaten its very existence. Ensuing dangers from climate change and population growth will further strain these resources. To stop disaster scenarios from happening, our only way is to manage these prized resources. Modeling programs, such as SWAT, are valuable tools in finding ways of combating food and water insecurity, and mitigating the impact of climate change and growing demands of resources. This Special Issue of Water is designed to show the results of analyses of scientists from all over the world in dealing with various environmental problems. The papers here are selected from the works presented at the 16th International SWAT conference held in Beijng. The information and analyses are intended to contribute to the development and implementation of effective soil and water management programs.